Total Cerebral Small Vessel Disease Score and Cerebral Bleeding Risk in Patients With Acute Stroke Treated With Intravenous Thrombolysis - Du, Houwei; Wu, Sangru; Lei, Hanhan; Ambler, Gareth; Werring, David J.; Li, Hangfeng; Chen, Yangui; Chen, Dongping; Yuan, Qilin; Fang, Shuangfang; Chen, Ronghua; Zhang, Yixian; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the association of total cerebral small vessel disease (cSVD) score with the risk of intracerebral hemorrhage (ICH) in patients with acute ischemic stroke who received intravenous thrombolysis (IVT) using recombinant tissue-plasminogen activator (rt-PA). Methods: We retrospectively reviewed clinical data from two stroke registries of patients with acute ischemic stroke treated with IVT. We assessed the baseline magnetic resonance (MR) visible cSVD markers and total cSVD score (ranging from 0-4) between patients with and without ICH after IVT. Logistic regression analysis was used to determine the association of total cSVD score with the risk of ICH after IVT, adjusted for cofounders selected by least absolute shrinkage and selection operator (LASSO). We additionally performed an E-value analysis to fully explain away a specific exposure-outcome association. ROC (receiver operating characteristic) curve analysis was used to quantify the predictive potential of total cSVD score for any ICH after IVT. Results:. Among 271 eligible patients, 55 (20.3%) patients experienced any ICH, 16 (5.9%) patients experienced a symptomatic ICH (sICH), and 5 (1.85%) patients had remote intracranial parenchymal hemorrhage (rPH). Logistic regression analysis showed that the risk of any ICH increased with increasing cSVD score (per unit increase, adjusted odds ratio [OR] 2.03, 95% CI 1.22-3.41, P = 0.007). Sensitivity analyses using E-value revealed that it would need moderately robust unobserved confounding to render the exposure-outcome (cSVD-any ICH) association null. ROC analysis showed that compared to the National Institutes of Health Stroke Scale (NIHSS) score alone, a combination of cSVD and NIHSS score had a larger area under the curve for any ICH (0.811, 95% CI 0.756-0.866 versus 0.784, 95%CI 0.723-0.846, P=0.0004). Conclusions: Total cSVD score is associated with an increasing risk of any ICH after IVT and improves prediction for any ICH compared to NIHSS alone.